Análisis farmacobotánico, dinámica de polifenoles y actividad biológica de Baccharis spicata (Lam.) Baill. - Asteraceae - - Agudelo, Ignacio Jorge (2019)
Baccharis spicata (Lam.) Baill (Asteraceae) is employed as a substituent of medicinal\nspecies of the Baccharis genus known as ?carquejas?, though the scientific evidence\navailable nowadays is scarce regarding its efficacy, safety and quality.\nThe aim of this thesis is to know the proportion of samples of medicinal herbs rotulated as\n?carqueja? that contain B. spicata, to know the best organ and moment for the recollection in\norder to obtain the highest amount possible of polyphenolic compounds and to assess the\ntoxicogenetic safety and the efficacy against different models of liver pathologies.\nWe report that B. spicata is present in more than half of the samples labelled as ?carqueja?\nsold in stores, and that the highest amount of polyphenolic compounds can be found in the\nleaves during spring, which contains 5-caffeoylquinic acid, 3,5-dicaffeoylquinic acid and\nrutin as its main compounds.\nRegarding to the biological activities, the infusion of leaves does not induce genetic damage\nas determined in bacterial and cellular assays. Also, the infusion of leaves inhibited the\nreplication of the hepatitis B virus in the HepG2.2.15 cell line and produced an increase in the\nbile flow when administered to healthy animals.